Bakteri patogen pada telepon genggam mahasiswa fakultas kedokteran Universitas Airlangga angkatan 2014 - Ribka Brillyand Angeli Mboe; Marijam Purwanta; Lilik Djuari (Universitas Syiah Kuala, 2020)
Recently people use mobile phone in the places that have a high density of microorganisms such as in the hospital, in the kitchen, and in the toilet. Some studied stated that mobile phones played a role in transmission of pathogenic bacteria. Brady et al., reported that 9% to 25% of mobile phones were contaminated with pathogenic bacteria. This research was based on experimental laboratory. The samples were mobile phone, swabbed by wet sterile cotton bud and placed on MacConkey Agar plate and Blood Agar plate. The isolated bacteria were checked by Gram stained. Catalase test for Gram-positive cocci bacteria and specific biochemical test for Gram-negative bacilli bacteria were used to determine the genus of the bacteria. The samples were mobile phone belong to 2014-entering-year students of Medical Faculty of Airlangga University. The sampling method was simple random sampling. This experiment found that 100% of the samples were Staphylococcus spp. positive, 3,3% were Shigella spp. positive and 3,3% were Proteus spp. positive. From this experiment could be concluded that mobile phone belong to 2014-entering-year students of Medical Faculty of Airlangga University were contaminated by pathogenic bacteria. The result of this experiment found that Shigella spp. and Proteus spp. were pathogenic bacteria on mobile phone belong to 2014-entering-year students of Medical Faculty of Airlangga University.